2015
DOI: 10.1080/01652176.2015.1023404
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coliO157:H7 in wild boars (Sus scrofa) and Iberian ibex (Capra pyrenaica) sharing pastures with free-ranging livestock in a natural environment in Spain

Abstract: Background: Wild ungulates have greatly increased in abundance and range throughout Europe. This new situation presents a concern for public health because many wild ungulates are known reservoirs of zoonotic pathogens. Objectives: In this work, we tested for the presence of the zoonotic pathogen Escherichia coli O157:H7 in free-ranging livestock and sympatric wild boars (Sus scrofa) and Iberian ibex (Capra pyrenaica) in NE Spain from 2009 to 2011. In addition, antimicrobial resistance and virulence factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 24 publications
(17 reference statements)
1
13
0
Order By: Relevance
“…In this study, we found that 1.9% (9/474) of the wild deer and 0.7% (3/426) of the wild boar in Japan carried STEC O157. A similar prevalence in other wild animals has been reported in many studies in Europe and America [11,13,36,43,45,46], suggesting that the prevalence of STEC O157 among wild deer and boar in Japan was similar to prevalence in other countries.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…In this study, we found that 1.9% (9/474) of the wild deer and 0.7% (3/426) of the wild boar in Japan carried STEC O157. A similar prevalence in other wild animals has been reported in many studies in Europe and America [11,13,36,43,45,46], suggesting that the prevalence of STEC O157 among wild deer and boar in Japan was similar to prevalence in other countries.…”
Section: Discussionsupporting
confidence: 83%
“…The prevalence of STEC O157 in wild deer has been reported to be 0.3-2.4% in the United States [13,43,46], 1.5% in Spain [45], and 2.3% in Japan [47]. The prevalence of STEC strains in wild boar was also reported to be 0-3.4% in Spain [11,36,44] and 1.4% in Sweden [52]. Recently, Tomino et al [51] detected potential human pathogens including STEC O157 in wild deer and boar in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, STEC strains reported in wild birds (1Á3%), wild boars (3Á3%), deer (7Á0%) and muflons (100%) in Spain (Alonso et al 2017), and in wild canids (crab-eating fox) (14Á0%) in Brazil (Riboldi et al 2018). Finally, with related occurrence rates, EHEC pathotype was also described in wild boars and Iberian ibexes faecal samples in Spain (Navarro-Gonzalez et al 2015).…”
Section: Resultsmentioning
confidence: 96%
“…The presence of STEC in wild boar has been evaluated in several countries globally, including Switzerland (Wacheck et al., ), Belgium (Pierard, van Damme, Moriau, Stevens, & Lauwers, ) and Spain (Diaz‐Sanchez et al., , ; Navarro‐Gonzalez et al., ) and STEC were found in 9%, 27% and between 2.7 and 9.5% of samples tested, respectively. Additionally, STEC isolates were found in wild boar in Germany, although no prevalence determination was made in the study (Miko et al., ).…”
Section: Resultsmentioning
confidence: 99%